Stories of Resilience and Communication in the Face of Stigma - Winda Primasari; Aulia Diah Safitri; Miftakhudin Miftakhudin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2026)
This study explores the experiences of individuals with visual disabilities who often encounter difficulties in accepting themselves due to their physical conditions. It investigates the process of self-acceptance and the nature of their social interactions within the framework of interpersonal communication. The research specifically aims to understand how interactions with people in their surrounding environment contribute to and support the development of self-acceptance. Using a descriptive qualitative approach, the study involved interviews with four participants with visual disabilities—both low vision and total blindness—as well as three key informants who work as social workers. The interview data were recorded, transcribed, and subsequently coded for analysis. The findings indicate that five key aspects of interpersonal communication—openness, empathy, supportive attitudes, positive attitudes, and equality—play a significant role in fostering self-acceptance among individuals with visual disabilities. Overall, the study contributes to the development of communication studies, particularly in expanding understanding of interpersonal communication in relation to the self-acceptance process of people with visual impairments.